2020
DOI: 10.4103/ipj.ipj_37_19
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-induced serotonin syndrome

Abstract: Linezolid is an oxazolidinone antibiotic, which is a weak, reversible, nonselective monoamine oxidase A and B inhibitor; is known to increase serotonin levels, and has been implicated in the development of serotonin syndrome (SS). There is limited literature on the development of SS with linezolid, when used alone. In this report, we present the case of a 70-year-old female who developed features of SS while being treated with linezolid 600 mg twice daily for pneumonia. The SS in her case was managed with stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, the platelet count returned to normal after treatment with linezolid for 3 days.Factors that can cause thrombocytopenia include leukemia, related autoimmune diseases, drug-and vaccine-induced thrombocytopenia, and patients without associated diseases. 10 According to the criteria for assessing adverse drug reactions, the thrombocytopenia concentration in this case might have been caused by linezolid. It has been reported in the literature that linezolid-induced thrombocytopenia usually occurs within 10-14 days after the initiation of treatment.…”
Section: F I G U R Ementioning
confidence: 95%
“…However, the platelet count returned to normal after treatment with linezolid for 3 days.Factors that can cause thrombocytopenia include leukemia, related autoimmune diseases, drug-and vaccine-induced thrombocytopenia, and patients without associated diseases. 10 According to the criteria for assessing adverse drug reactions, the thrombocytopenia concentration in this case might have been caused by linezolid. It has been reported in the literature that linezolid-induced thrombocytopenia usually occurs within 10-14 days after the initiation of treatment.…”
Section: F I G U R Ementioning
confidence: 95%
“…When the syndrome is moderately severe, signs and symptoms include hypertension, hyperthermia, overactive bowel signs, inducible extremity clonus, ocular clonus, agitation, hypervigilance, and pressured speech. The recommended management for this syndrome is the suspension of linezolid with subsequent administration of cyproheptadine and supportive measures [21].…”
Section: Serotonin Syndromementioning
confidence: 99%
“…January-February-5(1): 2374-2378 C inducible extremity clonus, ocular clonus, agitation, hypervigilance, and pressured speech. The recommended management for this syndrome is the suspension of linezolid with subsequent administration of cyproheptadine and supportive measures [21]. Hypoglycemia Linezolid has monoamine oxidase (MAO) inhibitory properties, and MAO inhibitors have been reported to contribute to hypoglycemia.…”
Section: Reaction Synthesismentioning
confidence: 99%
“…Symptoms are also used to guide the differential diagnosis of the two syndromes; for example: in NMS, patients may have stiffness, rhabdomyolysis (characterized by muscle fiber destruction), and increased serum creatine phosphokinase (CPK) levels, which should not occur in SS [ 90 ]. However, some SS case reports show that patients present rigidity, sometimes associated with hyperreflexia [ 91 - 94 ] and increased serum CPK levels [ 92 , 95 , 96 ]. In the meta-analysis carried out by Werneke et al (2016), with all cases of SS published in the PubMed databases and Thomson Reuter's Web of Science from 2004 to 2014, they observed that in the 299 cases of SS included in the study, 45.4% (136 cases) had stiffness, and 14% had rhabdomyolysis (42 cases) [ 5 ].…”
Section: Reviewmentioning
confidence: 99%